Penerapan Algoritma K-Means Untuk Pendataan Obat Berdasarkan Laporan Bulanan Pada Dinas Kesehatan Kabupaten Lombok Timur - Suhartini, suhartini; wijaya, Lalu kerta; Pratiwi, Nur Arini (Infotek : Jurnal Informatika dan Teknologi, 2020)
Medicine is one of the most important components in terms of health both to prevent reducing or cure a disease or symptoms of the disease bydoing medication processing every month can be a source decision making to ensure the availability of more effective and efficient drugs. However, the implementation of medicine for the health services district in lombok east has been affected by the difficulties dealt with with drug data documentation that resulted in increased drug use, and the distribution of drugs was hampered not only. Therefore there needs to be a method that helps the system of drug-filing systems based on monthly reports. K-means is expected to be able to group monthly medications that can be used as a model for planning medical supplies the following year, and the information generated from them can be used as a recommendation in both community centers and hospitals to improve public health services. The criteria for the most drugs in the East Lombok District Health Office were 193 items. This is because the usage is seen the most from monthly usage. There are 2 slices of drug use there are 2 slices, namely the first drug with group number 4, the item is less use than group 1. Second, there are drugs with group 3 number, the item which has the least use of group 1 and group 2.DOI : 10.29408/jit.v3i2.2315